Optimal Intensity of Aerobic Exercise Training for Patient With Chronic Obstructive Pulmonary Disease (COPD): Systematic Review and Meta-Analysis - Christian James Ibrahim; Ari Natalia Probandari; Yusup Subagio Susanto; Jatu Aphridasari (Indonesian Society of Respirology (ISR), 2023)
Background: Intensity for aerobic exercise is unclear in patient with COPD. Previous systematic review comparing effects of different levels of training intensity was done in 2011 and did not reach any conclusion. We conducted this systematic review to see the differences in aerobic training intensity on various aspects of health in COPD patients with updated information. Method: We included RCTs, comparing the differences in intensity of aerobic training between groups. The primary search was done through Pubmed, Scopus, Science Direct, Proquest, and PEdro. The PEdro scale and Risk of Bias 2 tool was used to rate the studies. Lastly, we also rate the certainty of evidence using GRADE approach. The assessment was carried out by two reviewers independently. Data were extracted by one reviewer then evaluated by second reviewer. Results: We found and analysed data from four studies with total of 472 patients. The primary outcomes extracted were Disease-specific Health-Related Quality of Life (HRQoL), Activities of Daily Living (ADL), Functional exercise capacity, Dyspnea symptoms. There was a significant difference only in St George’s Respiratory Questionnaire (SGRQ) symptoms domain for HRQoL outcome (MD=5.53; 95% CI=1.08-9.97), favoured lower intensity group. No other significant results were found for any other outcomes/ outcome measures. According to GRADE, quality of the studies was very low to moderate. Conclusion: The evidence we collected is very limited and difficult to evaluate. Further research comparing higher intensity with lower intensity of aerobic training is needed.